Daily Activity of the Housefly, Musca domestica, Is Influenced by Temperature Independent of 3' UTR period Gene Splicing - Bazalova, Olga; Dolezel, David (G3 (Bethesda, Md.), 2017)
Circadian clocks orchestrate daily activity patterns and free running periods of locomotor activity under constant conditions. While the first often depends on temperature, the latter is temperature-compensated over a physiologically relevant range. Here, we explored the locomotor activity of the temperate housefly Musca domestica Under low temperatures, activity was centered round a major and broad afternoon peak, while high temperatures resulted in activity throughout the photophase with a mild midday depression, which was especially pronounced in males exposed to long photoperiods. While period (per) mRNA peaked earlier under low temperatures, no temperature-dependent splicing of the last per 3' end intron was identified. The expression of timeless, vrille, and Par domain protein 1 was also influenced by temperature, each in a different manner. Our data indicated that comparable behavioral trends in daily activity distribution have evolved in Drosophila melanogaster and M. domestica, yet the behaviors of these two species are orchestrated by different molecular mechanisms.
Keywords: Animals; Female; sestřih RNA; kryptochromy; teplota; RNA Splicing; ženské pohlaví; temperature compensation of circadian rhythms; introny; pohybová aktivita; časové faktory; Time Factors; locomotor activity; kondiční příprava zvířat; 3' nepřekládaná oblast; Houseflies; Introns; Circadian Rhythm; moucha domácí; messenger RNA; 3' Untranslated Regions; cirkadiánní rytmus; RNA, Messenger; Cryptochromes; Phylogeny; Temperature; regulace genové exprese; Genes, Insect; Male; Exons; transcription; Drosophila melanogaster; circadian clock genes; Physical Conditioning, Animal; hmyzí geny; Motor Activity; exony; promotorové oblasti (genetika); zvířata; mužské pohlaví; Gene Expression Regulation; Photoperiod; fylogeneze; Promoter Regions, Genetic; mRNA splicing; fotoperioda